Metode Penentuan Toleransi Cekaman Kekeringan Menggunakan Indeks Sensitivitas Kekeringan Pada Fase Kecambah Cabai (Capsicum annum L.) - Budiyanti, Tri; Indriyani, NLP; Riska; Kirana, Rinda; Suliansyah, Irfan; Harvani, Dini (Prosiding Sains dan Teknologi, 2024)
Drought stress can cause a decrease in crop production. The development of drought stress tolerant chili varieties can be done to overcome this problem. Several methods, including the drought stress selection method in the sprouting phase, can be carried out using Polyethylene glycol (PEG-6000) stress simulation. The drought sensitivity index (ISK) or stress susceptibility index (SSI) is used to select for drought stress tolerance in plants. This research aims to determine the level of drought stress tolerance of several chili genotypes at the sprouting stage based on the drought sensitivity index. The research used a complete randomized block design with 23 local West Sumatran chili genotypes treated with drought stress at the germination stage with 15% PEG and control (0% PEG). Based on the drought sensitivity index (ISK) criteria, the results of the screening of chili tolerance to drought using five variables obtained six genotypes which were included in the tolerant category, namely genotypes (7) Tanah Datar Green Bonsai, (6) 33 Taijan, (21) Akar Solsel , (18) Lolai Chili, (1) Tali and (5) CI Sijunjung. DM-2, Bukitinggi and Dhamasraya-1 chilies have the highest total ISK score which indicates they are susceptible to drought stress at the germination stage.